Lycorine hydrochloride inhibits cholangiocarcinoma through cholesterol biosynthesis and PTPN11 nuclear translocation - Fengyun Zhao; Shuxian Peng; Liming Zou; Mingtian Zhong; Yanni Huang; Ping Wang; Mingfang Ji; Xiaodong Ma; Fugui Li (Cell Communication and Signaling, 2025)
Abstract Background Intrahepatic Cholangiocarcinoma (ICC) is a highly aggressive malignancy with limited treatment options. Identifying novel therapeutic agents for ICC is crucial. Numerous natural compounds have demonstrated remarkable anti-tumor activities and can enhance the efficacy of chemotherapy. Thus, our study aimed to screen natural compounds for their anti-ICC effects. Methods A total of 640 natural compounds were screened using a cell viability assay to identify potential compounds that could inhibit the proliferation of ICC cells. The anti-ICC effects of Lycorine Hydrochloride (LY) were confirmed through cell proliferation, colony formation, cell cycle, migration, and invasion assays, as well as in xenograft models. Bioinformatics analyses and validation experiments (Quantitative real-time PCR, Western blot, and immunostaining assays) were utilized to investigate the roles of genes (SQLE, FDFT1, and PTPN11) in ICC. RNA sequencing and immunofluorescence staining were performed to elucidate underlying molecular mechanisms. Results LY was identified as a potential ICC inhibitor, exhibiting anti-ICC effects both in vitro and in vivo. Mechanistically, LY inhibited cholesterol synthesis in tumor cells by down-regulating the expression of SQLE and FDFT1. The knockdown of SQLE or FDFT1 significantly inhibited ICC cell proliferation and colony formation. RNA sequencing confirmed that inhibition of FDFT1 suppressed the cholesterol biosynthesis pathway, while SQLE inhibition affected specific oncogenic pathways. Additionally, immunofluorescence staining revealed that down-regulation of SQLE reduced PTPN11 expression and inhibited its nuclear translocation. Furthermore, pharmacological inhibition of SQLE and FDFT1 by LY significantly enhanced sensitivity to several common chemotherapeutic drugs for ICC. Notably, the combination of LY and Gemcitabine (GEM) displayed the most potent synergistic anti-tumor effect across various tumor types. Conclusion These findings identify Lycorine Hydrochloride as a promising treatment alternative for ICC and propose a novel combination strategy (LY + GEM) for treating multiple solid tumors.